Prevalence of depressive symptoms and associated factors in Brazilian older adults: 2019 Brazilian National Health Survey - Frederico Kochen Trevisan; Ritele Hernandez da Silva; Simone Farias Antunez Reis; Marui Weber Corseuil Giehl (Cadernos de Saúde Pública, 2025)
This study aimed to describe the prevalence of depressive symptoms and associated factors among older adults. A cross-sectional population-based study using data from the 2019 Brazilian National Health Survey was carried out. The prevalence of depressive symptoms was determined using the 9-item Patient Health Questionnaire (PHQ-9), and associations were tested according to sociodemographic, health and behavioral variables. Crude and adjusted prevalence ratios (PR) with 95% confidence intervals (95%CI) were calculated using Poisson’s regression. The overall prevalence of depressive symptoms was 10.7% (95%CI: 9.9; 11.5). Higher PHQ-9 scores were associated with female gender (PR = 2.11, 95%CI: 1.82; 2.44), lack of participation in religious activities (PR = 1.20, 95%CI: 1.07; 1.35), nonsmoking status (PR = 1.55, 95%CI: 1.32; 1.83), poor or very poor self-perceived health (PR = 7.55, 95%CI: 5.82; 9.80), and multimorbidity (PR = 2.26, 95%CI: 1.85; 2.75). Higher education (PR = 0.55, 95%CI: 0.42; 0.73), income (PR = 0.68, 95%CI: 0.54; 0.85), and physical activity (PR = 0.72, 95%CI: 0.57; 0.90) were found to be negatively associated with the outcome. The most prevalent depressive symptoms were: sleeping problems (24.8%, 95%CI: 23.8; 25.8), not feeling rested or willing/feeling without energy (14.5%, 95%CI: 13.7; 15.4), and being depressed/down/without perspective (10.5%, 95%CI: 9.7; 11.2). These findings highlight the importance of prioritizing the identification and treatment of depressive symptoms in older Brazilian populations, particularly given that one in ten older Brazilians experience depressive symptoms.